A cluster randomized trial of community mobilization to reduce methamphetamine use and HIV risk among youth in Thailand: Design, implementation and results. (August 2018) - Galai, Noya; Sirirojn, Bangorn; Aramrattana, Apinun; Srichan, Kamolrawee; Thomson, Nicholas; Golozar, Asieh; Flores, Jose M.; Willard, Nancy; Ellen, Jonathan M.; Sherman, Susan G.; Celentano, David D.
Abstract: Background: Use of methamphetamines (MA) and other stimulants have consistently been associated with HIV/STI risk globally. We evaluated a community mobilization intervention (Connect to Protect, C2P ® ) to prevent MA use among youth and reduce HIV risk behaviors through community structural changes. Design: A community-randomized trial in northern Thailand with matched districts randomized to C2P intervention or a standard voluntary counseling and testing (VCT) control. Intervention districts formed stakeholders' coalitions to plan tailored local prevention programs. Two independent random household samples of youth aged 14–24 were surveyed in 2009 and 2012. Lifetime and recent MA use was modeled with multilevel logistic regression. Results: Intervention initiatives included family-strengthening programs, school-based programs and opening a community drug treatment center. Control communities applied the government-led "war on drugs" approach in addition to youth and family programs. Baseline (N = 1077) and follow-up (N = 1225) samples included 47.5% females and 21.7% aged ≤16. Lifetime MA use in intervention districts reduced from 13.4% to 11.7% compared to reduction from 16.2% to 10.4% in the control districts (non-significant). In models, lifetime MA use was associated with: time (aOR = 0.6, 95%CI: 0.38–0.83), females (aOR = 0.2, 95%CI: 0.15–0.29), increasing age (aOR = 2.4, 95%CI: 1.40–4.20, ages 16–19; aOR = 3.5, 95%CI: 2.00–6.12, ages ≥ 20), and not being full-time students (aOR = 5.3, 95%CI: 3.77–7.37). Recent MA use showed similar results. Additionally, lifetime MA use was significantly associated with alcohol use, risky sexual behaviors and elevated depressive symptoms. Conclusions: Delay in developing and implementing specific prevention programs in the intervention districts slowed diffusion of the effect into the communities. Secular trends with contentious civil unrest and active drug-enforcement efforts in the control communities also contributed to the null intervention effect. Longer time and intensified efforts stressing a public health approach are needed to demonstrate the effectiveness of community mobilization in reducing substance use and HIV risk in this rural Thai community. Highlights: We developed a unique community-led intervention in Thailand targeting youth MA use. Intervention districts coalitions initiated school-based and drug treatment programs. There was no differential impact of the intervention on lifetime or recent MA use. Parallel law-enforcement activities in the control arm contributed to null results. Longer time is needed for effectiveness of community-mobilization intervention.